UTF 25 - Early bread wheat cultivar with white flour - Benin,Giovani (2020)
Abstract The wheat cultivar UTF 25 is recommended for wheat-growing regions 1 and 2 of Paraná and Santa Catarina states. It has a good disease resistance, early cycle, and high grain yield potential, with an average yield of 3.511 kg ha-1. It is classified as bread wheat with white flour.